INOVASI MEDIA PEMBELAJARAN FLASHCARD LAGU INDONESIA RAYA: TINJAUAN RELIGIUS, FILOSOFIS, DAN PSIKOLOGIS DI SEKOLAH DASAR - Nurul Ain, Saskia; Eva Betty Simanjuntak; Indri Khairunnisa Erwinsyah; Syahkira Sifah Nasution; Trisna Natalia Br Parapat; Selvi Simanjuntak (Universitas Negeri Medan, 2025)
Teaching the Indonesian national anthem, Indonesia Raya, in elementary schools often consists only of routine singing activities, so that students do not really understand the national values contained therein. This study introduces flashcards as a new learning tool reviewed from religious, philosophical, and psychological perspectives at the Al-Hidayah Education Foundation. The method used is descriptive qualitative with purposive sampling techniques involving 20 fourth-grade students and one classroom teacher. Information was collected through observation, interviews, and media testing, then analyzed by reducing the data, presenting it, and drawing conclusions using triangulation of sources and methods. The findings of this study indicate that flashcards can increase students' motivation, involvement, and understanding of the meaning of the national anthem. The learning process becomes more engaging, enjoyable, and appropriate for the level of children's cognitive development. From a religious perspective, songs are understood as a form of gratitude to God; from a philosophical aspect, they encourage character development and national awareness; while from a psychological perspective, they are in line with children's visual and interactive learning needs. In this way, flashcards have proven to be an effective tool as a creative medium for instilling national values and strengthening character education at the elementary school level.